Occurrence and Favorable Enrichment Environment of Lithium in Gaoping Coal Measures: Evidence from Mineralogy and Geochemistry - Peiliang Han; Fenghua Zhao; Dongna Liu; Qi Zhang; Qinqin Zhang; Shaheed Ullah (Applied Sciences, 2024)
The Carboniferous-Permian coal measure strata in the Qinshui Basin exhibit highly lithium (Li) enrichment, with substantial exploitation potential. To further explore the enrichment mechanism of lithium in coal measure strata, the No. 15 coal of the Taiyuan Formation from the Gaoping mine is taken as the research object, and its mineralogical and geochemistry characteristics are evaluated using optical microscopy, X-ray diffraction, scanning electron microscopy, inductively coupled plasma mass spectrometry, X-ray fluorescence, and infrared spectral. The results show that the No. 15 coal is semi-anthracite coal with low moisture, low ash, low volatility, and high sulfur. Organic macerals are primarily vitrinite, followed by inertinite, and liptinite is rare; the inorganic macerals (ash) are dominated by clay minerals (predominantly kaolinite, cookeite, illite, and NH4-illite), calcite, pyrite, quartz, siderite, gypsum, and zircon. The average Li content in the coal is 66.59 μg/g, with higher content in the coal parting (566.00 μg/g) and floor (396.00 μg/g). Lithium in coal occurs primarily in kaolinite, illite, cookeite, and is closely related to titanium-bearing minerals. In addition, Li in organic maceral may occur in liptinite. The No. 15 coal was formed in the coastal depositional system, and the deposition palaeoenvironment is primarily a wet–shallow water covered environment in open swamp facies; the plant tissue preservation index is poor, and aquatic or herbaceous plants dominate the plant type. The reducing environment with more terrestrial detritus, an arid climate, and strong hydrodynamic effects is favorable for Li enrichment in coal. The results have important theoretical significance for exploring the enrichment and metallogenic mechanisms of Li in coal.